Seroconversion and adverse reaction of live-attenuated (OKA strain) varicella vaccine - Yulchair Ramli; Sri Rezeki H A; Arwin P Akib (Paediatrica Indonesiana, 2003)
Background Live-attenuated varicella vaccine was used to pre-vent Shingle disease.Objective The aim of this study was to find out seroconversionrate and safety of this vaccine.Methods An open clinical trial was conducted on 313 children atCipto Mangunkusumo Hospital, Jakarta between March and Octo-ber 1998. The data were analyzed to distribution frequency andtables.Results Only 43 out of 356 (12.1%) children had positiveantivaricella antibody before vaccination. Seroconversion exami-nation by indirect immunoflouresence method was done only onrandomly 150 of 313 (50%) children due to financial limitation. Itwas found that 99.3% of patients had positive seroconversion.Among 298 children who were followed, the nature of symptom ofadverse reaction was mostly general than local. Only one patienthad local symptom after vaccination that appeared within 7 daysof the follow up period.Conclusion Varicella vaccine (OKA strain) gives highseroconversion rate with minimal adverse events